Uma proposta de sequência didática para jogos combinatórios - Gomes, Ygor Franzotti de Barros (2015)
This work presents a didactic sequence about combinatorial games for Regular School. The topics are "Games", "Numbering System", "Divisibility", “Symmetry" and "Problems" .Each chapter contains a contextualized theoretical development, solved problems and proposed ones, containing the appropriate answers and tips for solutions.